Self Regulation Learning (SRL) dan Budaya Akademik Terhadap Motivasi Berprestasi Mahasiswa - Firsty Oktaria Grahani; Starry Kireida Kusnadi; Aironi Zuroida; Berlian Nur Cafsah; Diandra Maharani (Universitas Muhammadiyah Jember, 2023)
Achievement motivation is needed by students in undergoing education at tertiary institutions in order to achieve the desired achievements. Trigger motivation is influenced by intrinsic and extrinsic factors. Learning self-regulation is one of the intrinsic factors that influence student efforts in designing achievement targets and goals while academic culture is an extrinsic factor that influences the effectiveness of achievement motivation. The purpose of this study was to determine the effect of SRL and academic culture on achievement motivation and to obtain an overview of SRL and academic culture on student achievement motivation. Quantitative descriptive research with a sample of 131 students at